Value orientations of Filipino families in a suburban community as reflected in their preferences in financial and related management situations - Salcedo, Erlinda Nacino 1946-; Dizon, Angelita M. (1972)
The purposes of this study are: (1) to determine if a pattern of value orientations existed among Filipino families; (2) to determine specific value orientations reflected by their preferences in financial and related management situations; (3) to determine the rank order of these value orientations; and (4) to determine if such factors as sex, location in the community, age, educational attainment, nature of occupation, income, length of marriage, number of children, stage of family cycle, region of origin, and length of stay in the community are related to these value orientations. Only four of the five value orientations postulated by Kluckhohn and Strodbeck (1961) have been considered in this study, namely, the Relational, Time, Activity, and Man-nature. This study assumes that behavior of Filipino families in financial and related management situations manifest certain values which they consider important. The study also assumes that those values are measurable. Furthermore, it is hypothesized that some variables considered in this study are related to value orientations. This study is limited to four value orientations among 90 Filipino families living in a suburban community as reflected in their choices of financial and related management situations. Both husband and wife were interviewed if not simultaneously, separately, but at close intervals. An interview schedule consisting of two parts was used in gathering the data. Part I dealt with the family background characteristics of the respondents, and Part II included forty family financial and related management situations, each measuring a value orientation. Then situations were formulated for each value orientation. The final data for this study were gathered in Barrio Santolan, Pasig, Rizal. The barrio is eight kilometers west of the town proper of Pasig and four kilometers east of the town of Marikina. The barrio used to derive its income from agriculture. Today, there are eight factories located in the area, and the majority of the families are non-farmers. The findings indicate that the respondents have definite patterning of value orientation alternatives to most of the situations studied. However, husbands and wive tend to differ in degree of agreement to most items. Analysis of the intra-item patterning reveal that husbands and wives have rank-order preferences as to value orientation alternatives, depending upon the specific situation. Collateral significantly preferred over Lineal over Individual. Lineal is slightly preferred to Individual. In the Time orientation aspect, the present is significantly chosen over Future and Past, while the Future is likewise significantly more popular than the Past alternative. In the Activity value orientation alternatives, the Being-in-Becoming was significantly preferred to Doing and Being, while Doing was significantly preferred to Being. Mastery-over-nature was significantly preferred to Harmony-with-and-Subjugation-to-nature alternatives. Similarly, Harmony-with-nature was significantly more popular to Subjugation-to-nature- alternative. The following conclusions drawn from the analysis of the data of this study seemed justified. Relational value orientation. As educational attainment increased, there was a corresponding and significant increased preference for the Collateral alternative. However, with increase of age, length of marriage, and length of stay in the community, there was a significant decrease in preference for the Collateral type. Preference for the Lineal alternative significantly increased with increase in length of marriage and number of children. The individual alternative was not significantly related to any of the factors considered in this study. Time value orientation. Preference for the Present alternatives significantly decreased with age, but increased significantly with increase in educational attainment. Choice of the Past alternative was negatively correlated with educational attainment and income, but significantly increased with number of children. Length of stay in the community was positively but not significantly related to preference for the Future alternative. Activity value orientation. Preference for the Being-in-Becoming and Doing alternatives are not significantly related to any variable. However, the preference for the Being alternative significantly decrease with the decrease in length of stay in the community. Man-nature value orientation. Preference for the Subjugation-to-nature alternative decrease significantly with increase in educational attainment and income. However, it is positively and significantly preferred as length of marriage and number of children increase. Harmony-with-nature alternative decrease significantly with age, while preference for the Mastery-over-nature alternatively increase significantly with educational attainment. The conclusions drawn from the result of this study substantiate the assumption that value orientations are reflected in the preferences of Filipino families regarding management situations. The hypothesis that value orientations would be related to certain variables considered in this study is supported. The results suggest some implications and recommendations for educators, community development workers, and social scientists. Suggestions for the improvement of the measuring instrument used in the study of value orientations are also presented.
Thesis (M.A.)--University of the Philippines.
Keywords: Family -- Philippines; Worth